Analisis Kesulitan Guru dalam Mengimplementasikan Pembelajaran Tematik pada Kurikulum 2013 di SD Negeri Tigarun - Arifina, Lutfi Azzah; Vchananda, Syalsyabila alisyia; Putri, Julianor Vatika; Widiawati, Olivia; Rahmah, Yunita; Aslamiah, Aslamiah; Yulandra, Rianty; Pratiwi, Diani Ayu (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the difficulties of teachers in implementing thematic learning in SD Negeri Tigarun, Tigarun Village, Juai District, Balangan Regency. Using a qualitative approach with a case study method, this research collected data through observation, structured interviews, and documentation. The research subjects were all class teachers at SD Negeri Tigarun. The results showed that the main difficulties of teachers in thematic learning lie in three aspects: lesson planning, lesson implementation, and integrating Basic Competencies (KD) from various subjects. Other inhibiting factors in implementing thematic learning are limited time for teachers to prepare lesson plans, lack of adequate learning media, and difficulties in linking themes with local wisdom.